PENGARUH ROA, SIZE, RISIKO LIKUIDITAS, RISIKO KREDIT, RISIKO SUKU BUNGA, DAN RISIKO MODAL TERHADAP CAR PADA BANK UMUM YANG TERDAFTAR DI BEI PERIODE 2008–2013 - Yunialdo, Fredy Herman; Prasetiono, Prasetiono (Faculty of Economics and Business Diponegoro University, 2015)
In general, the bank can be interpreted as a financial institution whose business activities are collecting funds from the public and channel the funds back to the community and provide other banking services.In carrying out its functions of banks must maintain capital adequacy ratio or CAR. This study uses secondary data derived from the annual financial statements, involving 23 banking Â companies listed on the Indonesian Stock Exchange in the period 2008 to 2013. Sampling using purposive sampling method with the provisions of the company's financial statements. Using the method of pooled sample data so obtained were 138 observations. Data analysis using multilinear regressionofordinary leastsquare test tool which includes the classic assumption test which consists of test multicollinearity, normality test, autocorrelation test and heteroscedastisity test. While hypothesis testing is done by F test and t test. The results of these tests found that partially Size, Liquidity Risk, and Interest Rate Risk (IRR) Â significantly influence while Return On Asset (ROA), Credit Risk, and Capital Risk does not significantly affect Capital Risk towards Capital Adequacy Ratio (CAR). The coefficient determinant (RSquare) is 0,303 which means 30,3% Capital Adequacy Ratio (CAR) variation explained by Return On Asset (ROA), Size, Liquidity Risk, Credit Risk, Interest Rate Risk (IRR) and Capital Risk towards Capital Adequacy Ratio (CAR),whereas 69,7% explained by another variables whis is not followed.